The significant effects of puberty on the genetic diathesis of binge eating in girls. Issue 8 (31st May 2017) - Klump, Kelly L.; Culbert, Kristen M.; O'Connor, Shannon; Fowler, Natasha; Burt, S. Alexandra
Abstract: Objective: Recent data show significant phenotypic and genetic associations between ovarian hormones and binge eating in adulthood. Theories of hormonal risk focus on puberty and the possibility that hormone activation induces changes in genetic effects that then lead to differential risk for binge eating in postpuberty and adulthood. Although this theory is difficult to test in humans, an indirect test is to examine whether genetic influences on binge eating increase during the pubertal period in girls. Prior work has shown pubertal increases in genetic influences on overall disordered eating symptoms, but no study to date has examined binge eating. The present study was the first to examine these increases for binge eating. Methods: Participants included 1, 568 female twins (aged 8–25 years) from the Michigan State University Twin Registry. Binge eating and pubertal development were assessed with self‐report questionnaires. Results: Twin moderation models showed significant linear increases in genetic effects from prepuberty (5%) to postpuberty (42%), even after controlling for the effects of age and body mass index. Discussion: Results provide critical support for increased genetic influences on binge eating during puberty. Additional studies are needed to identify hormonal mechanisms and fully test contemporary models of ovarian hormone risk.